The Construction of Artificial Intelligence as an International Security Issue in the United Nations Agenda 2025 - Ahmad Ali Afandi; Badrus Sholeh (Department of International Relations, Brawijaya University, 2025)
This study analyzes how the United Nations (UN) constructs the issue of artificial intelligence (AI) as part of international security through a constructivist approach. In recent years, AI has developed rapidly and raised global concerns regarding technological misuse, disinformation, and potential threats to political stability and human rights. This phenomenon has driven the emergence of various global governance initiatives, including discussions at the UN Summit of the Future 2025. Using qualitative methods and constructivist discourse analysis, this research examines official documents, speeches by the Secretary-General, and reports from institutions such as UNIDIR, WEF, and OECD. The analysis is conducted through three stages: description, interpretation, and explanation. The findings reveal that the concept of “AI security” does not arise naturally from the nature of the technology itself but is shaped through social processes and normative discourses among global actors. The UN acts as a norm entrepreneur promoting the values of responsible AI and collective security, while states interpret these norms according to their own identities and interests. Thus, AI security is a social construct reflecting the interaction between ideas, interests, and identities within the international system. This study contributes to the strengthening of non-traditional security studies by demonstrating how technological issues can be understood as arenas for the formation of global norms and state political identities.